TIGRIGNA FOLKTALE: "A GUILEFUL LIAR DECEIVES A SAINT" - Ghebrai , Isaias (International Journal of Linguistics, 2022)
A Guileful Liar Deceives a Saint is a proverb as well as the title of a folktale in Tigrigna oral tradition. The full context of the tale explicates the proverb and does more. The nexus between the proverb and the tale helps a reader or a listener of the folktale to compare the message of the proverb with the message of the folktale. This tale explores what some of the concerns of the Tigrigna people were in the past. Among the pertaining issues of this folktale are: the need for telling the truth, the deplorableness of falsehood, the need for critical thinking, the consequences of lies, the need for trust, the importance of communication, the need to beware of the feeling of entitlement, the aspect of communality in Tigrigna society, the extent to which liars' schemes could reach, the end result of evilness, the need for not judging by outside looks, aspects of monastic life in Tigrigna community, and the role of the endowment of the tale.